Relationships between large-scale climate modes and the South Atlantic Ocean wave climate - Ramos, M. S.; Farina, L.; Faria, S. H.; Li, C. (Progress in Oceanography, 2021)
Modes of variability in ocean wave conditions are coupled to atmospheric circulation changes due to exchange of energy and momentum at the interface. Here, we explored for the South Atlantic Ocean the relations between three main climate oscillations (El Niño Southern Oscillation [ENSO], Southern Annular Mode [SAM], and Pacific Decadal Oscillation [PDO]), four wave parameters (significant wave height [Hs], mean wave period [Tm], and zonal [Dm,x] and meridional [Dm,y] wave direction components) and wind parameters (wind speed [WS10], and zonal [u10] and meridional [v10] components). For this purpose, we regressed wind and wave parameters against the oscillation indices to create spatial composites of slope values, quantifying the correlation between wave parameters and indices. An EOF (empirical orthogonal function) analysis was also carried out to identify variability modes of wave parameters and to associate them to each climate index. The combining effects of ENSO and SAM were analysed by calculating Hs, Tm and wind speed anomalies for the periods in which the phases of these oscillations co-occur. We found important correlations not only with the dominant mode of variability, but also with secondary and even quaternary modes. For ENSO, negative correlations between the Oceanic Niño Index (ONI) and Hs, Tm, and Dm,x in the northwest part of the South Atlantic Ocean were highlighted, with a decrease (increase) of up to 8 cm of Hs per ONI unit in El Niño (La Niña) events. We established positive correlations also between ONI and these wave parameters in subtropical regions along the western African coast during austral summer, which were intensified by negative SAM. During autumn, however, we observed La Niña positive Hs anomalies for this region, which were also intensified by negative SAM. Finally, we found new, significant correlations between South Atlantic Ocean wave climate and SAM. We determined that the PDO index has negative correlations with Hs and Tm, while directional components present stronger ...